Mechanics of the solid state - Rimrott, F. P. J. (Friedrich Paul Johannes), 1927-; Schwaighofer, Joseph, 1924- (Heritage., 1968)
Collected in this volume are nineteen selected contributions written by twenty-six scholars in the field, in honour of their teacher and colleague, Professor Joseph Marin.